#### Answer

$\frac{1}{4}$

#### Work Step by Step

$-\frac{1}{2}-(-\frac{3}{4})=-\frac{1}{2}+\frac{3}{4}=\frac{3}{4}-\frac{1}{2}=\frac{3}{4}-\frac{1\times2}{2\times2}=\frac{3}{4}-\frac{2}{4}=\frac{3-2}{4}=\frac{1}{4}$

Published by
Pearson

ISBN 10:
0321825535

ISBN 13:
978-0-32182-553-7

$\frac{1}{4}$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.